Pengembangan Sistem Pemetaan Otomatis Entity Relationship Diagram Ke Dalam Database - Michelle Larassati Ayusmara Latukolan; Achmad Arwan; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One phase in database design for developing a software is a database design, this phase created based on conceptual and relational models. The process that is quite difficult is when mapping databases. When user requirement changed, it will have an impact on the design of the Database System that has been made before. In addition, a complex database structure, when experiencing changes will take a lot of time to be manually mapped. Based on these problems, A system was created to map the database model in the form of ERD so that it can be directly used on MySQL databases. With the goal to ease the mapping process, this system uses Chen's notation. This notation is the most used notation in the data modeling tool because it is easily read and interpreted. But this notation is rarely used by the ERD mapping application. This system uses seven steps of Entity Relationship diagram mapping so that it complies with the rules of Software Engineering. The system is made by web-based, using object-oriented programming, and using the Codeigniter framework. The system develop 16 requirement that has been tested using white-box and black-box testing in order to get best result in Chen's notation ER diagram mapping and the final testing results as expected, and compatibility testing got 95% valid result.